2016
DOI: 10.1016/j.addbeh.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse in emerging adulthood: Association of dopamine and serotonin receptor genes with impulsivity-related cognition

Abstract: Impulsivity predicts alcohol misuse and risk for alcohol use disorder. Cognition mediates much of this association. Genes also account for a large amount of variance in alcohol misuse, with dopamine and serotonin receptor genes of particular interest, because of their role in motivated behavior. The precise psychological mechanisms through which such genes confer risk is unclear. Trait impulsivity conveys risk for alcohol misuse by influencing two distinct domains of cognition: beliefs about the reinforcing ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Substance use expectancies exist as early as childhood (Dunn & Goldman, 2000) and have been shown to predict high-risk drinking in adolescents (Christiansen, Smith, Roehling, & Goldman, 1989;Vik, Carrello, Tate, & Field, 2000). Leamy, Connor, Voisey, Young, and Gullo (2016) showed that the increased reward drive of the BAS found in people high in DT traits was a significant predictor of positive substance use expectancies which, in turn, was associated with increased alcohol misuse. Lee, Oi, Greeley, and Baglioni (2003) demonstrated five dimensions of substance use expectances, three of which may be specifically important for the link between DT traits and substance use and preference: increased confidence, cognitive enhancement, and tension reduction.…”
Section: Substance Use Expectanciesmentioning
confidence: 99%
“…Substance use expectancies exist as early as childhood (Dunn & Goldman, 2000) and have been shown to predict high-risk drinking in adolescents (Christiansen, Smith, Roehling, & Goldman, 1989;Vik, Carrello, Tate, & Field, 2000). Leamy, Connor, Voisey, Young, and Gullo (2016) showed that the increased reward drive of the BAS found in people high in DT traits was a significant predictor of positive substance use expectancies which, in turn, was associated with increased alcohol misuse. Lee, Oi, Greeley, and Baglioni (2003) demonstrated five dimensions of substance use expectances, three of which may be specifically important for the link between DT traits and substance use and preference: increased confidence, cognitive enhancement, and tension reduction.…”
Section: Substance Use Expectanciesmentioning
confidence: 99%
“…This creates a self-fulfilling prophecy that is reinforced when realised. Several studies now empirically support these relationships in a range of populations [2124].…”
Section: Introductionmentioning
confidence: 97%
“…It is proposed that this creates a self-fulfilling prophecy that is reinforced when realised. Several studies now empirically support the bSCT model in a range of populations (Gullo, St. John, et al, 2014;Harnett, Lynch, Gullo, Dawe, & Loxton, 2013;Kabbani & Kambouropoulos, 2013;Leamy, Connor, Voisey, Young, & Gullo, 2016;Papinczak et al, in press).…”
Section: Discussionmentioning
confidence: 90%
“…The authors did not find evidence for the polymorphisms moderating the relationships between impulsivity, cognitions and alcohol use. However, there was a novel finding of the direct impact of the HTR2A gene, as the presence of this gene was associated with lower positive alcohol expectancies, higher drinking refusal self-efficacy and reduced alcohol misuse (Leamy, Connor, Voisey, Young, & Gullo, 2016). Together these findings suggest that there may be some impact of genes implicated in alcohol risk on alcohol use onset and dependence and this may indirectly affect factors within the bSCT model.…”
Section: )mentioning
confidence: 93%
See 1 more Smart Citation